PELAYANAN KONSELOR DALAM MENGATASI MASALAH SISWAPERSPEKTIFGENDER - Nurfarida Deliani (Kafa`ah: Journal of Gender Studies, 2011)
Education is an effort to make all Indonesia people more intelligent, without differenciation of gender. The female people are human being who has unique characteristic. They more introfet than male, and keep their problem by their self. Principally, all problems that we have must be alleviation.The counseloris aprofession who has responsible for all eviating the problems faced byall people. By the principle of confidentiality in their hand, the counseloris obliged to receive complaint sor problems faced by  their clients. With a variety of approaches available, counselor seeks to eliminate the student problems, in or derthey cangrow thand develop to reach for a better life.Keywords : Counselor, and WomenCopyright © 2011 by Kafa`ah All right reservedDOI : 10.15548/jk.v1i2.76